2021
DOI: 10.18502/ijm.v13i5.7417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COVID-19 antibody response with using three different tests

Abstract: Background and Objectives: In this study, the performance of three different commercial antibody assays for COVID-19 was examined and parameters affecting the antibody response were investigated. The correlation of patients’ chest CT results, procalcitonin, CRP, and D-dimer levels with the antibody response were retrospectively evaluated. Materials and Methods: COVID-19 antibodies were detected by three commercially available assays in each patient. Two of the assays were rapid immunochromatographic test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…higher than ours but were very close to the values mentioned in the literature[3,9,[12][13][14][15][16][17][18][19][20][21].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…higher than ours but were very close to the values mentioned in the literature[3,9,[12][13][14][15][16][17][18][19][20][21].…”
supporting
confidence: 91%
“…This shows that some patients might have been positive for some antibodies, while others might have been negative. As can be seen in Figures 1 and 2 [3,9,[12][13][14][15][16][17][18][19][20][21]. In one of these studies, the sampling time median was 12 days after symptom onset, which was earlier than ours, and it was mentioned that both the blood sample collection timing and the disease severity could potentially affect the sensitivity of the assays [3].…”
Section: Original Articlementioning
confidence: 72%
See 1 more Smart Citation
“…Wellinghausen et al [30] explained the lower SARS-CoV-2 IgG in asymptomatic patients by the lower viral load demonstrated by high Ct values. In addition, Appak et al [32] concluded that higher Anti-SARS-CoV-2 antibodies are correlated with lower Ct values. This is in accordance with our results that the level of anti-RBD-spike antibodies correlates positively with presenting symptoms.…”
Section: Discussionmentioning
confidence: 99%